Türk iş hukukuda iş güvencesi tazminatı - Sancı, Zekeriya (My University, 2010)
Türk İş Hukukunda İş Güvencesi Tazminatı ilk olarak 4773 sayılı Kanun ve daha sonra da 4857 sayılı İş Kanununda yerini almıştır. İş güvencesi tazminatından yararlanabilmek için öncelikle İş Kanununda düzenlenen iş güvencesi hükümlerinden yararlanabiliyor olması gerekir. İş güvencesi hükümlerinin kabul edilmesiyle birlikte işverenin fesih hakkı sınırlanmış, geçerli neden olmadan yapılan fesihlere karşı işe iade davası yolu açılmış, mutlak işe iade söz konusu olmadığı için de yargılama sonucu işveren tarafından işe başlatılamayan işçiye iş güvencesi tazminatının ödenmesi öngörülmüştür. İşe iadenin söz konusu olabilmesi için öncelikle işçinin kanuni süre içerisinde işe iade davası açması gerekir. İşe iade kararına rağmen işçi işe başlatılmazsa, iş güvencesi tazminatı söz konusu olacaktır. Kanuni düzenlemede iş güvencesi tazminatının alt ve üst sınırı mutlak olarak belirlendiğinden, işçi lehine de olsa hiçbir şekilde düzenleme yapılmayacaktır. İş güvencesi tazminatının miktarı belirlenirken iş sözleşmesinin fesih sebepleri ve işçinin kıdemi göz önünde bulundurulacaktır. Ödenmeyen iş güvencesi tazminatının tahsili genel haciz yoluyla yapılacaktır. İş güvencesi tazminatından yararlanabilen işçiler, diğer tazminatlardan yaralanamayacaktır. İş güvencesi tazminatından vergi kesilmemesi kanunla düzenlendiğinden vergi kesilmeyecektir. İş güvencesi tazminatı, ücret sayılabilecek bir kazanç olmaması ve işe başlatılmayan sigortalının sigortalılık niteliği kalmaması sebebiyle de prime tabi tutulmayacaktır.

The Job Security Indemnity took place in Turkish Labor Law first in the Labor Code no. 4773 and then Labor Code no. 4857. In order to be entitled to the Job Security Indemnity one is first of all to be able to benefit from the Job Security Provisions regulated in the Labor Law. With the acceptance of the Job Security Provisions, the Employer’s Right for Annulment has been restricted; the way to a lawsuit for reemployment shall be opened against such annulments that have been made without acceptable reasons; and, since absolute reemployment is out of the question, it has been stipulated that the employee that is not reemployed by the employer in spite of the Court’s Verdict, be paid Job Security Indemnity. For the reemployment, the concerned worker is first to litigate within the legal period a lawsuit for reemployment. If, despite of the verdict for the reemployment, the concerned worker is not reemployed, then Job Security Indemnity shall be in question. As the minimum and maximum limits of Job Security Indemnity have been absolutely determined in the Legal Regulation, no arrangement shall be made by any means even if it is to the benefit of the worker. The reasons of Annulment of an Indenture and the Employee’s Gratuity shall be taken into account in the determination of the total sum of the Job Security Indemnity. The collection of unpaid Job Security Indemnity shall be made through General Confiscation. Workers entitled to Job Security Indemnity shall not be able to benefit from the other indemnities. As it has been regulated by Law that no tax shall be levied on the Job Security Indemnity, no tax shall be imposed thereon. Again, Job Security Indemnity shall not be subjected to any premiums, for it is no such an income as shall be considered as wages and the insured person that is not employed shall not bear the qualities of being insured.
Keywords: Çalışma Ekonomisi; Hukuk; İş Hukuku; İş Hukuku_Türkiye